DYNAMICS OF STUDENTS' SELF-REGULATED LEARNING WITHIN ECOLOGICAL MULTI-USER VIRTUAL-ENVIRONMENT - Fiel'ardh, Khalifatulloh (2013)
This study examined the dynamics of students' self-regulated learning within Multi-User Virtual Environment (MUVE). A blended learning activity within a MUVE-assisted ecology science curriculum was implemented to a sample of high school students. Qualitative data collection and analysis was embedded within a one-group posttest-pretest experiment to provide a better insight on how self-regulated learning fostering conceptual understanding of causality concepts within MUVE-based curriculum. 32 students from a bilingual private school in Bandung were purposively chosen as participants of this study. Participants were required to complete two quantitative instruments: the motivated strategy for learning biology questionnaire (MSLQ-B); a self-report instrument to measure students' self-regulated learning and test of students' conceptual understanding of causal pattern in ecosystem; a type of achievement test to assess students understanding of the causal pattern concept in ecosystem, before and after the intervention. Quantitative data analysis showed that intervention had an adequate impact to both self-regulated learning, as well to conceptual understanding in causality. The qualitative data analysis that acquired from interview, observation and content analysis, expanded the experimental outcomes by providing information on how the help-seeking was the most commonly used learning strategy. A low group engagement level could also be reported, and it implied that a competitive instead of collaborative learning atmosphere emerged. Pathway analysis showed that the self-regulated learning component significantly affect students' conceptual understanding. KEY WORDS: Self-Regulated Learning, Conceptual Understanding, Causal Patterns in Ecosystem, Multi-User Virtual Environment. Penelitian ini bermaksud untuk mempelajari bagaimana dinamika kemandirian belajar siswa dalam Multi-User Virtual Environment (MUVE). Kegiatan blended learning diaplikasikan dalam pembelajaran ekologi berbantu MUVE terhadap sekelompok siswa SMA. Pengumpulan serta pembahasan data kualitatif disisipkan dalam desain penelitian one-group posttest-pretest experiment untuk memperoleh pemahaman tentang bagaimana kemandirian belajar membantu siswa untuk memahami konsep hubungan sebab-akibat dalam pembelajaran berbantu MUVE. 32 siswa dari sekolah swasta bilingual di Bandung secara purposif dipilih sebagai partisipan dalam penelitian ini. Para siswa mengisi dua instrumen kuantitatif: motivated strategy for learning biology questionnaire (MSLQ-B); sejenis angket tertutup untuk mengukur kemandirian belajar siswa serta, test of students' conceptual understanding of causal pattern in ecosystem; sejenis tes prestasi untuk mengases pemahaman siswa tentang pola-pola hubungan sebab-akibat dalam ekosistem. Analisis data kuantitatif menunjukkan bahwa pembelajaran dengan MUVE menyebabkan perubahan yang cukup baik pada kemandirian belajar siswa, serta pemahaman mereka tentang konsep hubungan sebab-akibat. Hasil analisis data kualitatif yang diperoleh melalui wawancara, observasi serta analisis konten, menjelaskan temuan eksperimental dengan memberikan informasi bahwa mencari-bantuan adalah strategi yang paling banyak digunakan siswa dalam pembelajaran tersebut. Rendahnya keterlibatan siswa untuk mengikuti kerja kelompok dalam pembelajaran memberi implikasi bahwa lingkungan belajar kompetitif yang terbentuk, bukan lingkungan belajar kolaboratif. Analisis jalur me-nunjukkan bahwa komponen-komponen kemandirian belajar secara signifikan ber-pengaruh terhadap pemahaman konseptual siswa. KATA KUNCI: Kemandirian Belajar, Pemahaman Konsep, Pola-pola Hubungan Sebab-Akibat dalam Ekosistem, Multi-User Virtual Environm